A Model of Digital Vo-Book with Crossword for Teaching and Learning Vocabulary in Seventh Grade Junior High School t Blitar: Research and Development - Julia Ike Darmayanti; Dian Fadhilawati; Adin Fauzi (Universitas Islam Balitar, 2022)
This research objectives are to develop a model of Digital Vo-Book with Crossword for Teaching and Learning Vocabulary, to find out the appropriateness of Digital Vo-Book with Crossword for Teaching and Learning Vocabulary, and to know the teachers' and students' perceptions toward the use of development Digital Vo-Book with Crossword for Teaching and Learning Vocabulary in Seventh Grade Junior High School. This research adapted Sugiyono's R & D model. These research problems consisted of six steps: (1) data collections and finding potential and problem, (2) design and development, (3) expert validation and revision, (4) teachers’ and students’ perceptions, (5) evaluation by experts and revision, and (6) final product and publication. The result of material validation 90.6% and media validation 85.7% included in the